Strategi Efektif Penguasaan Kosakata Bahasa Inggris bagi Siswa SMA di Lhokseumawe dan Aceh Utara - Kurniawati, Kurniawati; Rizki, Dini; Yulisda, Desvina; Hanif, Hanif; Fariadi, Dedi; Marina, Marina; Kamila, Raisya; Rahmah, Chatrine Aulia (Universitas Malikussaleh, 2025)
Vocabulary mastery is a fundamental aspect of English language learning. Students who have a limited vocabulary will have difficulty communicating orally and in writing. This community service activity was carried out to identify challenges in vocabulary acquisition and develop effective and fun strategies to improve students' English vocabulary mastery at SMA Negeri 1 Dewantara Aceh Utara and SMK Negeri 7 Lhokseumawe. This service activity involves counseling and the application of technology-based learning methods, especially the use of social media, which is expected to increase students' motivation and competence in mastering English vocabulary. This activity provides English vocabulary learning strategies that can be applied by students for long-term English learning.